ANALISIS KELAYAKAN USAHA KERIPIK TETTE DI DESA BLUMBUNGAN KECAMATAN LARANGAN KABUPATEN PAMEKASAN - M. Juniar Fajrus Shalah; Joko Priyono (CV. Denasya Smart Publisher, 2024)
This study aims to evaluate the income, revenue, and viability of the tette chip industry from the financial and manufacturing processes in Blumbungan Village, Larangan District, Pamekasan Regency. This kind of study is known as descriptive research. This study's analytical methods include total production costs, revenues, income, and calculations of company feasibility utilizing ROI, R/C, and B/C ratios. Six informants from the Tette chips company in Blumbungan Village, Larangan District, Pamekasan Regency participated in this study. They were selected using a purposive sample method. Based on the research findings, the six informants who owned Tette chips businesses had an average total cost of IDR 1,016,797, an average income of IDR 2,185,000, and an average income of IDR 1,168,203. Using the B/C ratio to calculate business feasibility yielded an average result of 1.16 when B/C > 0, an average result of 16% when ROI > 0%, and an average result of 2.16 when R/C > 1. Based on the findings of these computations, it is possible to operate and grow the tette chip industry in Blumbungan Village, Larangan District, Pamekasan Regency.